Technological Advancements of Insoluble Dietary Fiber from Food By-Product Processing: A Review - Domenico Mammolenti; Francesca Romana Lupi; Noemi Baldino; Domenico Gabriele (Foods)
Insoluble dietary fibers (IDFs) represent one of the most promising candidates for novel food formulations, since they can be produced from a wide range of food by-products and wastes, have health benefits, and often enhance the rheology and stability of foods. Recently, the most innovative engineering and processing aspects of these attractive ingredients have received considerable attention. The present work is aimed at enlightening the technological state of the art regarding IDFs (much less investigated than soluble fibers, as discussed in this review). The review begins with a brief but crucial discussion on the definition of this type of dietary fiber by highlighting the raw materials, functional properties, physiological activity, and stabilization capacity in food products. The analysis of the rheological methods dedicated to the technical investigations of these ingredients and recent advancements are discussed. Finally, food processing technologies used in the formulation of foods containing insoluble IDFs, such as homogenization techniques, are discussed.